Answer:
<u>3</u><u>6</u><u>cm</u>
Step-by-step explanation:
2l + 25
l=14cm, w= 4cm
2(14cm+4cm)=
28cm + 8cm=
<u>36cm</u>
Combine. Note that one positive and one negative = one negative
-2.1 + (-5.9) + (-3.7) = -2.1 - 5.9 - 3.7 = -11.7
-11.7 is your answer
hope this helps
Answer:
I think it's 4.89897948557
Step-by-step explanation:
Answer:
C
Step-by-step explanation:
12²+24²=144+576=720≠26²(676)
The remainder from the division of the algebraic equation is -53/8.
<h3>What is the remainder of the algebraic expression?</h3>
The remainder of the algebraic expression can be determined by using the long division method.
Given that:
![\mathbf{f(x) = \dfrac{x^3 - 6x^2 + 3x - 1}{2x-3}}](https://tex.z-dn.net/?f=%5Cmathbf%7Bf%28x%29%20%3D%20%5Cdfrac%7Bx%5E3%20-%206x%5E2%20%2B%203x%20-%201%7D%7B2x-3%7D%7D)
where:
Using the long division method, we have:
![\mathbf{= \dfrac{x^2}{2} +\dfrac{-\dfrac{9x^2}{2}+3x -1 }{2x-3}}](https://tex.z-dn.net/?f=%5Cmathbf%7B%3D%20%5Cdfrac%7Bx%5E2%7D%7B2%7D%20%2B%5Cdfrac%7B-%5Cdfrac%7B9x%5E2%7D%7B2%7D%2B3x%20-1%20%7D%7B2x-3%7D%7D)
![\mathbf{= \dfrac{x^2}{2}-\dfrac{9x}{4} +\dfrac{-\dfrac{-15x}{4}-1 }{2x-3}}](https://tex.z-dn.net/?f=%5Cmathbf%7B%3D%20%5Cdfrac%7Bx%5E2%7D%7B2%7D-%5Cdfrac%7B9x%7D%7B4%7D%20%2B%5Cdfrac%7B-%5Cdfrac%7B-15x%7D%7B4%7D-1%20%7D%7B2x-3%7D%7D)
![\mathbf{= \dfrac{x^2}{2}-\dfrac{9x}{4} -\dfrac{15}{8}+\dfrac{-\dfrac{53}{8} }{2x-3}}](https://tex.z-dn.net/?f=%5Cmathbf%7B%3D%20%5Cdfrac%7Bx%5E2%7D%7B2%7D-%5Cdfrac%7B9x%7D%7B4%7D%20-%5Cdfrac%7B15%7D%7B8%7D%2B%5Cdfrac%7B-%5Cdfrac%7B53%7D%7B8%7D%20%7D%7B2x-3%7D%7D)
![\mathbf{= \dfrac{x^2}{2}-\dfrac{9x}{4} -\dfrac{15}{8}-\dfrac{53 }{8(2x-3)}}](https://tex.z-dn.net/?f=%5Cmathbf%7B%3D%20%5Cdfrac%7Bx%5E2%7D%7B2%7D-%5Cdfrac%7B9x%7D%7B4%7D%20-%5Cdfrac%7B15%7D%7B8%7D-%5Cdfrac%7B53%20%7D%7B8%282x-3%29%7D%7D)
Therefore, we can conclude that the remainder is -53/8.
Learn more about the division of algebraic equations here:
brainly.com/question/4541471
#SPJ1